A mediatory role of finance education in perception of chosen economic aspects in family and non-family firms - Zajkowski, Robert (Research Papers of Wrocław University of Economics, 2018)
Proper goals setting respects the current market circumstances, considers assessment of facts, respects various options and takes into consideration their consequences. Different decisions in companies are often taken fast, under stress, when emotions or other factors are likely to influence their results. The paper considers three aspects: self-assessment of the companies’ performance related to the industry, economic goals and economic education. The aim is to investigate whether education can mediate the interrelation between self-assessment of companies’ performance and salience of their economic goals. With the use of linear regression models of mediation and correlation coefficients it was pointed out that the self-esteem of companies’ performance compared to the sector as a factor of financial decision is mitigated by economic education
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 519, s. 184-194
Keywords: company’s objectives; economic education salience; mediations models; cele przedsiębiorstwa; znaczenie edukacji ekonomicznej; modele mediacji